Digital Workers of the World Unite! A Framework for Critically Theorising and Analysing Digital Labour - Christian Fuchs; Marisol Sandoval (tripleC: Communication, Capitalism & Critique)
The overall task of this paper is to elaborate a typology of the forms of labour that are needed for the production, circulation and use of digital media. First, we introduce a cultural-materialist perspective on theorising digital labour. Second, we discuss the relevance of Marx’s concept of the mode of production for the analysis of digital labour. Third, we introduce a typology of the dimensions of working conditions. Fourth, based on the preceding sections we present a digital labour analysis toolbox. Finally, we draw some conclusions. We engage with the question what labour is, how it differs from work, which basic dimensions it has and how these dimensions can be used for defining digital labour. We introduce the theoretical notion of the mode of production as analytical tool for conceptualizing digital labour. Modes of production are dialectical units of relations of production and productive forces. Relations of production are the basic social relations that shape the economy. Productive forces are a combination of labour power, objects and instruments of work in a work process, in which new products are created. We have a deeper look at dimensions of the work process and the conditions under which it takes place. We present a typology that identifies dimensions of working conditions. It is a general typology that can be used for the analysis of any production process.